The Azadiarachta indica, A natural pharmaceutical agent: Review Artical - Naheed, Rashda; Nazir, Muniba; Farhat , Fozia; Kausar, Abida (European Journal of Applied Sciences, 2020)
Since the origin of mankind, the use of plants and their derivatives remains an important aspect of human life to cure various ailments. Such pharmaceutical uses of plants are the cheaper and safe sources for disease management against the expensive allopathic drugs with various side effects. At present the use of traditional medicines is not gaining favors from masses but the rapidly increasing pharmaceutical industry is also shifting itself from the synthetic chemicals towards the natural extracts. The Azadiarachta indica is one of the most important and extensively used medicinal plants. Its uses as antiseptic agent and as cure and preventive remedy have been known since remote past. The extracts of A. indica have a proven anti- diabetic, anti-oxidant, bactericidal, anti- termite, pesticide activities. This plant can be used to treat various intestinal ailments. It has a proven wound healing capacity. Various types of tumors are being treated by the phytochemicals derived from this miracle tree. Its leaves bark and fruit constitute very useful natural components that can be used to cure various ailments. The oil of Azadiarachta has a significant importance in cosmetic industry. Biologically active compounds are isolated from different parts of A. indica like meliacin, nimbidin, gedunin, salanin, nimbolides, valassin, nimbin and Azadirachtin are present in A. indica oil.